2017
DOI: 10.1016/j.envexpbot.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-intensity blue radiation can regulate flowering, but not extension growth, of several photoperiodic ornamental crops

Abstract: When the natural photoperiod is short, lighting at the end of a day (day extension) or during the middle of a night (night interruption) can regulate flowering through intricate photoreceptive pathways. Phytochromes primarily absorb red (R; 600 to 700 nm) and far-red (FR; 700 to 800 nm) radiation and mediate flowering and photomorphogenesis. Although blue (B; 400 to 500 nm) radiation does not influence flowering at a low intensity, it can be well absorbed by photoreceptors such as cryptochromes and, to a lesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Although blue radiation is best absorbed by cryptochrome (cry) and phototropin (phot) photoreceptors, it is also weakly absorbed by phy [26]. Meng and Runkle [27] reported that phy-mediated responses can be controlled with moderate-intensity (~30 µmol•m −2 •s −1 ) blue light due to the secondary absorption peak of phy in the blue region of the spectrum. Furthermore, Liu et al (2012) showed that phy B controls the expression of both ERECTA and EXPANSIN family genes, which regulate cell expansion in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Although blue radiation is best absorbed by cryptochrome (cry) and phototropin (phot) photoreceptors, it is also weakly absorbed by phy [26]. Meng and Runkle [27] reported that phy-mediated responses can be controlled with moderate-intensity (~30 µmol•m −2 •s −1 ) blue light due to the secondary absorption peak of phy in the blue region of the spectrum. Furthermore, Liu et al (2012) showed that phy B controls the expression of both ERECTA and EXPANSIN family genes, which regulate cell expansion in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the plantlets growing under blue light conditions displayed superior growth performance compared with those growing under white light and red light conditions, including increased leaf number and leaf area, greater photosynthetic capacity, and the increased promotion of chloroplast development (Table 1 and Figure 1). Leaf morphological characteristics were reported to be greatly affected by different wavelengths of light [38,39]. In this report, the greatest leaf area was found under blue light conditions ( Table 1), implying that blue light promotes C. oleifera plantlet leaf growth.…”
Section: Influence Of Different Light Qualities On Growth and Physiolmentioning
confidence: 54%
“…Although low blue light (≈1–2 μmol m −2 s −1 ) can control physiological responses such as cotyledon opening through CRY2 (Lin et al ), effective regulation of flowering requires a much greater B photon flux density. For example, blue light regulated flowering of various ornamental species at a photon flux density of 30 μmol m −2 s −1 , but not at 2 μmol m −2 s −1 (Meng and Runkle , ). Similarly, in Arabidopsis, CRY2 activity under low blue light (≤1 μmol m −2 s −1 ) may not be responsible for the substantial flowering responses of high‐light‐grown cry2 mutants (Lin ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides R and FR light, blue light (400–500 nm) is also involved in photoperiodic pathways that regulate flowering of at least some species. Although blue light did not influence flowering of several floriculture crops at 2 μmol m −2 s −1 (peak = 462 nm, PPE = 0.53), it did when its photon flux density increased to 30 μmol m −2 s −1 (peak = 450 nm, PPE = 0.48; Meng and Runkle , ). It is mainly absorbed by cryptochromes (CRY1 and CRY2), is weakly perceived by phytochromes and activates phototropins, zeitlupe, flavin‐binding kelch repeat F‐box, and LOV kelch protein (Yanovsky and Kay , Huché‐Thélier et al ).…”
Section: Introductionmentioning
confidence: 96%